Membangun Udar Asumsi Menuju Kampung Moderasi Beragama Yang Moderat di Desa Kletek - Marianus Teti (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
The approach used in this research is a descriptive qualitative approach. The tools used to obtain data are observation sheets and interview sheets. Meanwhile, the methods used are observation and interviews. The results of the research show that the Kletek village community has established religious moderation since Islam entered the Keletek area. The researcher realizes that this paper is still far from perfection, therefore the writer really hopes for criticism and suggestions from all readers.